Tuning properties and dynamic range of type 1 vomeronasal receptors - Haga-Yamanaka, Sachiko; Ma, Limei; Yu, C. Ron (Frontiers in Neuroscience, 2015)
The mouse vomeronasal organ expresses chemosensory receptors that detect intra-species as well as inter-species cues. The vomeronasal neurons are thought to be highly selective in their responses. The tuning properties of individual receptors remain difficult to characterize due to the lack of a robust heterologous expression system. Here, we take a transgenic approach to ectopically express two Type 1 vomeronasal receptors in the mouse vomeronasal organ and characterize their responses to steroid compounds. We find that V1rj2 and V1rj3 are sensitive to two sulfated estrogens and can be activated by a broad variety of sulfated and glucuronidated steroids at high concentrations. Individual neurons exhibit narrow range of concentration-dependent activation. Collectively, a neuronal population expressing the same receptor covers a wide dynamic range in their responses to sulfated estrogens. These properties recapitulate the response profiles of endogenous neurons to sulfated estrogens.